Investigating the Adsorption Mechanism of Expired Esomeprazole as a Corrosion Inhibitor on Carbon Steel in Desalination Water - Bakari, Ibrahim; Al Madani, Mohammed; Abdullah, Taha; Gebril, Abdussalam (Journal of Pure & Applied Sciences, 2024)
The impact of expired esomeprazole (C₁₇H₁₉N₃O₃S) as an inhibitor on the corrosion behaviour of carbon steel in desalination water was investigated using the weight loss technique. It was discovered that the corrosion rate of the carbon steel specimens decreased with increasing inhibitor concentrations. Based on the results obtained in the Jepril & Bakari (2022) study, isotherm models were utilized to investigate the adsorption mechanism of expired esomeprazole on the surface of carbon steel in the current work. Thermodynamic parameters were also considered. With a correlation coefficient (R²) better than 0.9, the results showed that the inhibitor's adsorption on the surface followed the Langmuir, Freundlich, Adejo-Ekwenchi, and El-Awady adsorption isotherms. Physisorption was identified as the mechanism of adsorption.